2023
DOI: 10.1038/s43247-023-00977-1
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt, climate-induced increase in wildfires in British Columbia since the mid-2000s

Marc-André Parisien,
Quinn E. Barber,
Mathieu L. Bourbonnais
et al.

Abstract: In the province of British Columbia, Canada, four of the most severe wildfire seasons of the last century occurred in the past 7 years: 2017, 2018, 2021, and 2023. To investigate trends in wildfire activity and fire-conducive climate, we conducted an analysis of mapped wildfire perimeters and annual climate data for the period of 1919–2021. Results show that after a century-long decline, fire activity increased from 2005 onwards, coinciding with a sharp reversal in the wetting trend of the 20th century. Even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
2
11
0
Order By: Relevance
“…The analyses in this study showed that the MPB-induced tree mortality in BC, Canada, exerted a significant influence on fire occurrence and particularly large fire occurrence at a landscape level, even while considering environmental factors that are critically associated with fire characteristics. Because large fires account for 97% of the burned area in BC, we can conclude that MPB-induced tree mortality also contributed to the sharp increase in area burned in BC since about 2003, which has largely been attributed to changing climate (Parisien et al, 2023).…”
Section: Discussion Mpb Outbreaks Influenced Large Fire Occurrencementioning
confidence: 94%
See 1 more Smart Citation
“…The analyses in this study showed that the MPB-induced tree mortality in BC, Canada, exerted a significant influence on fire occurrence and particularly large fire occurrence at a landscape level, even while considering environmental factors that are critically associated with fire characteristics. Because large fires account for 97% of the burned area in BC, we can conclude that MPB-induced tree mortality also contributed to the sharp increase in area burned in BC since about 2003, which has largely been attributed to changing climate (Parisien et al, 2023).…”
Section: Discussion Mpb Outbreaks Influenced Large Fire Occurrencementioning
confidence: 94%
“…If the initial attack is unsuccessful, additional extended attack resources are allocated to most fires, although a small proportion of fires in remote areas receive a modified response (mainly observation). The area burned by wildfires increased since about 2003 (Parisien et al, 2023) (Figure 2b), mostly due to large LCF (≥100 ha burned area) (Figure 2c).…”
Section: Study Areamentioning
confidence: 99%
“…However, there are several drawbacks to this strategy. The protection ability of hardwood trees is limited before leafout, a period during which a significant number of fires can occur within the boreal forest (Parisien et al 2023). Furthermore, not all boreal sites can support hardwood species due to specific soil characteristics (Marchais et al 2022).…”
Section: Solution 3: Making Forest Landscapes More Resistant To Firementioning
confidence: 99%
“…Accurate prediction of the atmospheric environment and radiative forcing of the climate requires an improved understanding of the composition and optical properties of biomass burning aerosols, which contain a significant amount of light-absorbing organic components termed brown carbon (BrC). As the frequency and intensity of wildfires increase as a result of a warmer and drier climate, BrC becomes a profound contributor to the overall radiative forcing. This is attributed to its capacity to absorb solar radiation within the UV and visible wavelengths. , Additionally, the widespread use of biomass fuels and practices of agricultural burning in developing countries amplifies BrC emissions and its significance. The upsurge in BrC aerosols from biomass burning (BB) disturbs various climate and atmospheric processes, including long-range transport of atmospheric pollutants, cloud condensation and ice nucleation, alterations in snow and ice albedo, and reduced photodegradation rates. The extent to which BB-BrC aerosols influence these processes remains uncertain, which makes it challenging for atmospheric models to accurately project their global impact both presently and in the future.…”
Section: Introductionmentioning
confidence: 99%